Development and evaluation of virtual reality technology for the NTU Campus - Vitanoglou, Dimitrios (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Αγρονόμων και Τοπογράφων Μηχανικών, 2017)
The intention of this dissertation is to develop and evaluate a Virtual Reality technological tool for the campus of National Technical University of Athens. After thorough theoretical research and practical investigation on virtual tour software and applications we are going to develop an open-source virtual tour for the campus. Using this tool, visitors will have the ability to easily navigate anywhere within the campus, and get information regarding the most important campus facilities.